Kalinga Style Temple Art And Architecture Of Two Shaiva Temples Of The Coastal Belt Of Odisha In Eastern India - Dr. Ratnakar Mohapatra and Baikuntha Majhi (International Journal of Advanced Science and Technology, 2020)
The temple of Hara-Ganeshvara is an important Shaiva shrine of the Praci Valley in the coastal belt of Odisha.  It is located at the village Raisa in the Kakatpur Block of the Puri district of Odisha in Eastern India. The artistic technique and architectural features of the Hara-Ganeshvara temple of Raisa and Grameshvara temple of Ghodatikili of the coastal-belt of Odisha are the main aspects of the Kalinga style temple architecture of Eastern India. In fact, a few Shaiva temples of the coastal-belt of Odisha are very important considering their artistic techniques and religious significance. The earlier art historians had not dealt with the Hara-Ganeshvara  temple  of  Raisa and Grameshvara temple of Ghodatikili in detail, for which, these two temples have been taken here for the scholarly work. The aim of the present article is to focus on artistic techniques and architectural features along with the religious significance of the Hara-Ganeshvara temple of Raisa and Grameshvara temple of Ghodatikili of the coastal-belt of Odisha in Eastern India. Methodologically, both the primary and secondary sources have been used for the writing of this article.